Morphological rationale of mesenchymal stem cells in the local treatment of experimental chronic purulent-necrotic wounds - S. V. Slobodianyk; S. D. Khimich; S. V. Vernygorodskyi; V. S. Shkolnikov (Zaporozhye State Medical University, 2022)
Aim: to study morphological changes in healing of chronic purulent-necrotic wounds in rats with local use of 0.025 % decamethoxine solution and mesenchymal stem cells. Materials and methods. The experimental study was performed on 120 rats, which were divided into the following groups: I - control (without treatment); II - the use of classical wound healing (0.025 % decamethoxine); III - the use of clones of mesenchymal stem cells from the umbilical cord; IV - the use of clones of mesenchymal stem cells (cloned in inert gases). To assess morphological changes in chronic wounds, fragments measuring 0.5 cm × 1.0 cm × 1.0 cm were cut from the edges, followed by fixation in 10 % solution of neutral formalin. The microspeciments were prepared according to standard methods, histological sections 5-7 μm thick were stained with hematoxylin and eosin, basic brown, picrofuchsin according to van Gieson, Masson trichrome. The monoclonal antibodies (DAKO) with markers of intermediate filaments, mesenchymal cells and myofibroblasts - Vimentin (Clone V9), smooth muscle actin (αSMA, Clone 1A4), transmembrane protein of endothelial, stem cells and embryonic fibroblasts CD34 (Clone QBEnd 10) were used for immunohistochemistry. Results. The positive dynamics of chronic wounds healing, with the usage of 0.025 % decamethoxine solution only in the early stages (3-7 days) was determined with a decrease in inflammatory cellular infiltration, while MSC and MSC-IG were effective at all stages of research and confirmed by more intensive purification of the wound's surface from purulent and necrotic tissues, area of the wound reduction, granulation tissue formation and epithelialization acceleration. Conclusions. The use of MSCs and MSCs-IG creates favorable conditions for the normal course of regenerative processes and epithelialization of wounds with the activation of fibroblasts, which increases the effectiveness of chronic wound healing.